Interview with Shay Shaanan, STK Bio-Ag Technologies. (1st August 2022) - Blake, Robin; Shaanan, Shay
STK was previously known as Stockton. It was started in 1994 by Peter Tirosh who left a 23-year career at Makhteshim-Agan (now ADAMA) to set up his own generic company buying solutions from China and selling them into Latin America where he had good connections from his previous jobs. In 2004, Peter met two people from an Israeli start-up who told him about an idea to take tea-tree oil (TTO) from Pharma where it was used as an anti-bacterial agent and develop it into a solution for crop protection. Peter cooperated with them and after two years acquired the company. With money from Stockton they investigated TTO in more detail, worked out which diseases it controlled, how to formulate and use it, and in 2012, discovered that TTO controlled black Sigatoka (Mycosphaerella fijiensis), a key disease in LATAM bananas at the time. In 2015 there was a change in company ownership when a new CEO was appointed from outside the family. Following a $90 million investment from a public Chinese company, a new strategy was implemented in 2016 to develop and market botanical crop solutions for sustainable agriculture and aquaculture, and a rebranding in 2018 changed the company name from Stockton to STK to reflect the company's transition from its legacy generic agrochemicals business to its new focus on bio-ag technology and botanical-based solutions. The biofungicide Timorex Gold is its flagship product and based on TTO derived from the Melaleuca alternifolia plant. It is a broad spectrum biofungicide with preventive and curative properties recommended for the control of many important plant fungal and bacterial diseases in a wide range of fruit and vegetable crops. It can be used in rotations with other products, in tank mixes and as a solo formulation. The TTO extract contains over 100 compounds, some of which work synergistically and some which offer diverse modes of action.